2016
DOI: 10.1179/1743278215y.0000000037
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of corrosion properties of Ti–Nb–Cu alloy foam by electrochemical impedance spectroscopy method

Abstract: In the present study, highly porous Ti-Nb-Cu alloy foams were produced by a powder metallurgy method for biomedical implant (hard tissue) applications. Nb was added in order to stabilize the beta-Ti phase. Cu addition enhanced sinterability and reduced the sintering temperature of the alloy. Electrochemical corrosion behaviour of the Ti-Nb-Cu alloy specimens was examined by the electrochemical impedance spectroscopy method in an artificial saliva environment. Effects of porosity of the foam, Cu content of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…While Mutlu and Oktay in another study illustrated the decreasing in polarization resistance with increasing Cu content of the Ti-Nb-Cu alloy and the passive layer was a barrier for dissolution and improved the resistance through the charge transfer at the surface/medium interface with low Cu content, while the higher content produce {Ti}_{2}Cu phase which induce corrosion rates [23]. Also Mutlu et al in another study showed that increasing the Cu content for Ti-Nb-Cu alloys led to get higher corrosion current density and more negative corrosion potential [24].…”
Section: Corrosion Behaviormentioning
confidence: 97%
“…While Mutlu and Oktay in another study illustrated the decreasing in polarization resistance with increasing Cu content of the Ti-Nb-Cu alloy and the passive layer was a barrier for dissolution and improved the resistance through the charge transfer at the surface/medium interface with low Cu content, while the higher content produce {Ti}_{2}Cu phase which induce corrosion rates [23]. Also Mutlu et al in another study showed that increasing the Cu content for Ti-Nb-Cu alloys led to get higher corrosion current density and more negative corrosion potential [24].…”
Section: Corrosion Behaviormentioning
confidence: 97%
“…Although, most of them are studied in physiological solution, few studies are carried out in sea water, acid, and other solutions. The corrosion behavior of most Ti alloys in physiological solution is generally similar . Spontaneous passivation of these alloys in simulated body fluid is noted for most of these alloys.…”
Section: Introductionmentioning
confidence: 93%
“…Over the last decade, an impressive amount of literatures on corrosion of Ti alloys are documented . Although, most of them are studied in physiological solution, few studies are carried out in sea water, acid, and other solutions.…”
Section: Introductionmentioning
confidence: 99%
“…A flaw free oxide film on titanium should be resistant to hydrogen. For absorption of hydrogen from various chemical and biomedical environments, 7480 it is essential to undergo redox transformations (Ti 4+ + Ti 3+ ) inside the oxide or the making of ‘hydrogen windows’ at intermetallic sites. This is a prerequisite for the threshold potential of <–0.7 V (SCE) specified by Thomas and Schutz and presented in electrochemical measurements by Vezvaie et al 81 (see Figure 3(a)).…”
Section: Forms Of Hydrogen-induced Damagesmentioning
confidence: 99%